V. V. Vyurkov, A. B. Abuova, Y. N. Baymukanov - Vyurkov, V.V.; Abuova, A.B.; Baymukanov, Y.N. (Zhangir khan West Kazakhstan agrarian-technical university, 2017)
The favorable conditions for moistening during the growing of winter crops provided high yields of Saratovskaya 7 rye and soft wheat Zhemchuzhina Povolzhya, Kyzyl Biday and Arap. The main indicators of economic efficiency were soft wheat Zhemchuzhina Povolzhya, Saratovskaya 90, Arap, rye Saratov 7 and Triticale Balausa 8.
Наука и образования
Keywords: productivity; soft winter wheat; hard winter wheat; winter rye; winter triticale; winter barley